Review: Pyridinoline Cross Link as Biomarker Alveolar Bone Destruction - Dharmayanti, Agustin Wulan Suci (The Indonesian Journal of Dental Research)
Background: In Indonesia, prevalence of periodontal diseases was very high about 46 %. Periodontal diseases caused alveolar bone destruction. When bacteria attacked, bacteria product and host response stimulate collagen degradation, especially type 1 collagen. Collagen type 1 consisted pyridinoline cross link. Collagen degradation product will be excreted in bloodstream and urine. These products have advantage to detect alveolar bone destruction in periodontal disease early, because clinical and rongentnologis examination can detect advanced stage of alveolar bone destruction in periodontal diseases. Objective: The aim of this review was to know pyridinoline cross link as biomarker alveolar bone destruction. Literature review: Alveolar bone tissue was mineralization connective tissue. Alveolar bone can be destructed by dental plaque bacteria and also by host response. Dental plaque bacteria stimulated PMN and MMP releasing at inflamed gingival area. They caused collagen fibers of alveolar bone was degradated and caused releasing of pyridinoline crosslink in blood. Conclusion: Pyridinoline crosslink can be used as biomarker of alveolar bone destruction.